Chitosan and dextran stabilized GO-iron oxide nanosheets with high dispersibility for chemotherapy and photothermal ablation. Issue 5 (1st April 2019) - Zhang, Feng; Xie, Meng; Zhao, Yongwei; Zhang, Yanan; Yang, Mei; Yang, Na; Deng, Tongtong; Zhang, Mingmei; Xie, Jimin
Abstract: Iron oxide nanoparticle-modified graphene oxide nanosheets (GO-IONP) is a potential material for biomedical use, while its application is seriously limited due to its poor dispersibility under physiological conditions. In this work, GO-IONP was stabilized by chitosan and dextran via layer-by-layer self-assembly to produce GO-IONP-CS/DEX nanocomposites for targeted drug delivery and photothermal ablation. After the modification, its hydrophilic performance was enhanced, with the aggregation under physiological conditions strongly improved and undesired non-specific protein absorption ratio drastically reduced. Nanocomposites could load DOX up to 140.1% and DOX-loaded nanocomposites performed a sustained and pH-dependent drug releasing behavior. Moreover, the magnetic nanocomposites can be internalized by A549 cells with a magnetically targeted drug delivery profile. Pure GO-IONP-CS/DEX had an excellent photothermal ablation effect with no obvious cytotoxicity, and GO-IONP-CS/DEX-DOX had a cytotoxicity that increased with drug dose. All in all, GO-IONP-CS/DEX had good prospects for the biomedical delivery application.